DETERMINING THE DEVELOPMENT POTENTIAL OF THE ELECTRICAL INDUSTRY (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This article examines the role of the electrical engineering industry in the modern economy, the trends in its development, and the prospects forexpanding this sector in Azerbaijan. The electrical engineering industry is not limited to the production and distribution of electricity but also encompasses high-tech fields such as electronics, automation, communications, and household appliances. The development of this sector plays an important role in increasing the level of industrialization in the country, expanding knowledge-intensive production, and shaping a competitive economic structure. The analysis of international experience shows that the development of the electrical engineering industry in countries such as the United States, China, Turkey, and others is closely linked to government support, investments in research and development (R&D), innovation, and digitalization policies. According to global market data, the compound annual growth rate (CAGR) in this sector is around 7%, and by 2029 the global market volume is expected to reach USD 5.58 trillion. In Azerbaijan, the electrical engineering industry is still in its formative stage. In recent years, enterprises such as ATEF Group, STP Global Cable, Gök-Nur Bakı LTD, Alov Zavodu, and Taube Electronics have played an important role in the development of the sector. However, the product range remains limited, and dependence on imports is still high. The main challenges include the deterioration of production assets, a low level of innovation activity, a shortage of qualified personnel, and non-compliance of product quality with international standards.The state strategies “Azerbaijan 2020”, “Azerbaijan 2030”, and “Green Energy”, as well as industrial parks and investment promotion mechanisms, create an important foundation for the development of the electrical engineering industry. The article proposes several measures, including the development of a national program, strengthening the financing of local production, providing tax and customs incentives, attracting brand-name ompanies, and promoting innovation. The electrical engineering industry holds strategic importance for the diversification of Azerbaijan’s non oil sector, the transition to “green energy,” and the strengthening of the country’s economic independence.